A Giant Neurovascular Lower Limb Fillet Flap Can Simultaneously Cover Pelvic and Abdominal Defects. Issue 12 (December 2017) - Osinga, Rik; Nowakowski, Andrej; Isaak, Andrej; Schaefer, Dirk J.; Fulco, Ilario
Abstract : Summary: The first description of simultaneous pelvic and abdominal soft-tissue reconstruction with a giant lower limb fillet flap after hip exarticulation and open abdomen is presented. The unfortunate circumstances of a 67-year-old female patient are described leading to soft-tissue necrosis over a periprosthetic femur fracture and open abdomen after emergency implantation of an aortic bifemoral Y-prosthesis because of thrombotic obliteration of the aortic bifurcation. After removal of the hip prosthesis, the neurovascular pedicled myocutaneous fillet flap of the entire left leg was raised and folded proximally at the level of the exarticulated joint of the hip and set into the pelvic and abdominal defect. A giant pedicled neurovascular myocutaneous fillet flap raised over the entire lower extremity is a safe, effective, durable, and sensation-preserving treatment to reconstruct combined pelvic and abdominal soft-tissue defects.